Development of tat - conjugated dendrimer for transdermal DNA vaccine delivery - Bahadoran, Azadeh; Moeini, Hassan; Bejo, Mohd Hair; Hussein, Mohd Zobir; Omar, Abdul Rahman (Canadian Society for Pharmaceutical Sciences, 2016)
PURPOSE: In order to enhance cellular uptake and to facilitate transdermal delivery of DNA vaccine, polyamidoamine (PAMAM) dendrimers conjugated with HIV transactivator of transcription (TAT) was developed.